2009
DOI: 10.1002/sia.3092
|View full text |Cite
|
Sign up to set email alerts
|

XANES characteristics of tribofilms generated by dithiophosphate additive in water at different test temperatures and durations

Abstract: Water-based lubricants and metal-working fluids are becoming more and more popular in modern manufacturing due to environmental concerns. Owing to the poor lubricating properties offered by pure water, additives are generally needed to improve the antiwear and extreme pressure properties. In the present work, the tribological behaviors of synthesized additives in water-based lubricants are studied for different durations and temperatures by a four-ball machine, and the worn surfaces were analyzed by scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…These atoms originate from oil additives and wear debris during engine operation. XANES spectra from the literature [56][57][58][59][60][61] for engine oil additives suggest sulfur oxidation states that differ from chemistries expected to be found in asphalts. Thus the peaks in XANES spectra have the potential to indicate the presence of REOB.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These atoms originate from oil additives and wear debris during engine operation. XANES spectra from the literature [56][57][58][59][60][61] for engine oil additives suggest sulfur oxidation states that differ from chemistries expected to be found in asphalts. Thus the peaks in XANES spectra have the potential to indicate the presence of REOB.…”
Section: Introductionmentioning
confidence: 93%
“…Ma et al 61 reported spectra for FeS, FeSO 4 , and an engine oil additive S=P(SH)(OR) 2 . The FeS and FeSO 4 peaks were consistent with those of Nicholls et al 58 The additive peaks at 2467.9 and 2475.4 eV are not present in the asphalt spectra, so the presence of this additive may be ruled out.…”
Section: Implications For Reobmentioning
confidence: 99%
“…Water-based liquids function excellently as lubricants for example in natural systems such as joints with a coefficient of friction that could be less than 0.002 [7]. Simply using water for biomedical applications is not sufficient to control friction and wear for man-made systems, as water has very poor lubricating properties related to the low viscosity [8] and related to the lack of possibilities form high performing boundary layers.…”
Section: Water-based Lubrication and Bio-medical Applicationsmentioning
confidence: 99%
“…1,2 However, many traditional additives, such as zinc dialkyldithiophosphates (ZDDP), are not environmentally friendly due to the high content of metal, phosphorus, and sulfur, which will exhaust the environmental pollutants. 3 It is urgent to develop new environmentally friendly additives containing lower phosphorus and sulfur, even phosphorus-free and ashless additives. Meanwhile, in the presence of oxygen and moisture, the hydrogen chloride generated from chlorine-containing additives will cause a severe corrosion to metal surfaces.…”
Section: Introductionmentioning
confidence: 99%